Fenomena Penggunaan Bahasa Asing dan Daerah Dalam Penamaan Tempat Usaha Di Kota Gorontalo - Nuramila Nuramila (Journal on Education, 2023)
Language as a communication tool to establish interaction between one and another is a tool that is needed or plays an important role in human daily activities. Language is very necessary, including the use of language in store names. The phenomenon that exists today is the presence of shop names that use foreign and regional languages. This is basically not in accordance with what is contained in the Act or even in the Presidential Regulation. The purpose of this research is to describe the phenomenon of the use of foreign and regional languages ​​in the naming of business places in the city of Gorontalo. This type of research is a qualitative research that is descriptive in nature in providing a description of phenomena in terms of sociolinguistics, namely studies of language and social studies or studies that link languages ​​with certain social groups as language users, in this case looking at language variations, namely the diversity of language types. used in naming shop names in Gorontalo City.